Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening di Kantor Kecamatan Cibiru - Aliya Desti Fitriany; Andhika Siddiq (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
Human resources are among the most valuable organizational assets, as their competencies and capabilities can be continuously developed to improve organizational effectiveness and achieve strategic objectives. Employee performance plays a critical role in enhancing productivity and organizational success. This study investigates the effects of work discipline on employee performance, with job satisfaction serving as an intervening variable, at the Cibiru Subdistrict Office. A quantitative approach was employed using survey data collected from 42 employees. The data were analyzed using Path Analysis to examine both the direct and indirect relationships among the variables. The results indicate that work discipline has a positive and significant effect on both job satisfaction and employee performance. In addition, job satisfaction positively and significantly influences employee performance. The findings further reveal that job satisfaction partially mediates the relationship between work discipline and employee performance. These results suggest that strengthening work discipline not only directly improves employee performance but also enhances job satisfaction, which further contributes to better performance outcomes. Therefore, organizations should promote a disciplined work environment while fostering employee satisfaction to achieve sustainable improvements in organizational performance.